Effects of financial development and institutional quality on innovation - Lee, Weng Chang (2016)
This study aims to examine the role of institutional quality and financial development in innovation activities using international data. This thesis is organized into three major parts namely institutions-innovation, finance-innovation and segregated finance-innovation nexus. The first part of this thesis examines the various roles of sub-component institutions (e.g., formal and informal institutions) in countries’ innovation activities. Most of the recent works only focus on the roles of formal institutions. However, informal institutions such as social capital are equally important in determining innovation as it could promote the culture of knowledge sharing and thus, encourage innovation activities as a whole. The sample consists of 62 developed and developing countries. The study adopts instrumental variable estimators, and the empirical results indicate that formal and informal institutions complement one another in determining countries’ innovations level. Moreover, the evidence suggests that innovation level tends to be higher in countries with higher social capital. Thus, focus should be given in improving formal and informal institution in promoting innovative activities. The second part of this thesis aims examine the non-linear relationship between financial development and innovation using panel system generalized method of moments (GMM) estimators. The motivation of this study is to resolve current disparities of finance-innovation relationship as suggested by previous literature. The sample countries consist of 75 developed and developing countries and the sample period covers from 1996 through 2010. The empirical results reveal an inverted Ushaped non-linear relationship between finance and innovation. This implies that finance enhances innovation only up to a certain level; beyond that level, further development of finance tends to adversely affect innovation. We incorporate the institution interaction term to examine its role in governing such relationship. The empirical results suggest that the pattern of the finance-innovation curve varies with different settings of institutional quality. Specifically, only countries with high institutional quality follow an inverted U-shape of the finance-innovation curve. Hence, we conclude that sound institutional quality is a prerequisite before financial development has any beneficial impact on innovation. This reflects the inefficiency of finance market in facilitating innovation activities in most developing countries. Finally, the third part of this thesis aims to validate the non-linear dynamic financeinnovation nexus using a panel data of 69 developed and developing countries. This study is to investigate the roles of different financial market in influencing innovation activities. The empirical results support the idea that there is a threshold effect in the finance-innovation relationship. This findings indicate that the level of credit market and equity market development is beneficial to a country’s innovation only up to a certain turning point, and development of the financial market beyond the turning point would impede innovation activities. In addition, this study incorporates the roles of market institutions (e,g market creating, market stabilizing, market regulating and market legitimizing) in overseeing the finance-innovation relationship. The findings suggest that market institutions especially market creating and market regulating institutions plays important role in the finance-innovation relationship. Overall, the findings of this thesis conclude that i) Informal institutions is compliment to formal institutions in promoting countries innovations. ii) Non-linear relationship was found between financial development and innovation which follows an inverted U-shape curve. Here, institutional quality plays an important roles in governing such relationship. Countries with sound institutional quality follow an inverted U-shape finance-innovation curve while countries with weak institutional quality follow a Ushape curve. iii) Non-linear relationship also found between credit-innovation and equity-innovation nexus. Coincidencely, it’s also follows an inverted U-shape curve. However, equity market development are found to have a lengthier beneficial impact compared to credit market development. Besides, it’s also found market institutions plays an important roles on finance leads innovation relationship.